Sustainable roadway construction: Economic and social impacts of roadways in the context of Ethiopia. Issue 1 (1st January 2021) - Habte, Tariku Dessu
Abstract: Sustainable roadway construction can be defined as the optimal use of resources during the roadway life-cycle reducing the economic and social impacts. Two means of improving the sustainability of roadways are the appropriate selection of pavement types to minimize the life cycle cost of pavement and to reduce the social impacts. Thus, this work is aimed at analyzing the economic and social impacts of the Jointed Concrete Pavement in comparison to the Hot Mix Asphalt pavement from the perspective of life cycle cost analysis. To achieve the aim of the research the following tasks had been performed; Comprehend the backgrounds of life cycle assessment and life cycle cost analysis via literature review and data collection; Verify types of pavement; Analyze and Quantify structural components of pavement; Estimate agency and social costs; Perform life cycle cost analysis for each type of pavement, and finally Interpret the outputs. Results show that the life-cycle costs of the Jointed Concrete Pavement have about 90% cost advantage over the Hot Mix Asphalt pavement. This is the result of the unique properties of cement concrete which give its durability and hence lower maintenance, social cost, and longer design life. Finally, this research is expected to bring a paradigm shift and to strengthen the life cycle costs that are being considered in the overall cost of the pavement structure rather than just looking at the initial investment cost during the economic feasibility study of road projects under Ethiopian Roads Authority custody.